FEATURES FOR TRANSPORT AND AIR MECHANICAL SYSTEMS OF DANGEROUS GOODS - Eugen Dumitru BUSA (Fiabilitate şi Durabilitate)
Transport of dangerous goods are regulated activities, they take place under the direction and control of the authorities and specialized bodies in an institutional framework determined by national and international law. Of economic, transport infrastructure is the crucial element without which both production and trade would become meaningless, it is an essential element of a civilization, is also a necessary accessory of other economic activities.